Study of calf health and management problems in urban and per-urban dairy farms of selected districts of East Wollega Zone of Oromia Regional State, Western Ethiopia - Tesfaye Mersha Cherinnat; Fayera Bodena Edossa (International Journal of Veterinary Science and Research - Peertechz Publications, 2023)
Calf care is not only essential for the sustenance of the dairy industry but is also essential for preserving and maintaining good-quality of germplasm. On the contrary, high levels of calf mortality have limited dairy herd expansion and genetic improvement in the study area. Therefore, the study was developed to evaluate the existing calf health and management problems and to assess the level of farmers' knowledge and calf health and management practices in the study areas. Thus, a cross-sectional study design was used and the study districts and peasant association were selected purposely where as the individual household was selected randomly using a systematic random sampling method. A total of 50 households were selected from the three districts and a detailed questionnaire survey format was designed to generate baseline information related to the calf health management system and major calf health problems. As the study result indicated diseases like blackleg, pneumonia, and internal and external parasites were the most dominant calves' health problems. About 50% of the respondents informed that most calf mortalities occurred due to pneumonia, blackleg, starvation, heartwater, diarrhea, and bloat. Even though all calves were getting access to colostrum feeding, they do not access the optimum level, and regarding calves' feed natural grass is categorized in the first rank where as concentrated feeds (ground maize, grain, noug cake) and food left over (local brewery by product and straw) were placed in the second and third rank, respectively. And all farmers in the study area have access to veterinary services, however, the accessibility is not uniform among the farmers. In general, as the study revealed there has been poor management practice regarding both feeding and housing of calves in the study area. Therefore, identifying economically important animal diseases and designing strategic preventive and control measures and improvement of calf management practices through awareness creation among farmers is valuable.